Production, analysis, and safety assessment of a soil and plant-based natural material with microbiome- and immune-modulatory effects - Parajuli, Anirudra; Mäkelä, Iida; Roslund, Marja I.; Ringqvist, Emma; Manninen, Juulia; Sun, Yan; Nurminen, Noora; Oikarinen, Sami; Laitinen, Olli H.; Hyöty, Heikki; Flodström-Tullberg, Malin; Sinkkonen, Aki (Academic Press, 2024)
It has been suggested that reduced contact with microbiota from the natural environment contributes to the rising incidence of immune-mediated inflammatory disorders (IMIDs) in western, highly urbanized societies. In line with this, we have previously shown that exposure to environmental microbiota in the form of a blend comprising of soil and plant-based material (biodiversity blend; BDB) enhances the diversity of human commensal microbiota and promotes immunoregulation that may be associated with a reduced risk for IMIDs. To provide a framework for future preclinical studies and clinical trials, this study describes how the preparation of BDB was standardized, its microbial content analysed and safety assessments performed. Multiple batches of BDB were manufactured and microbial composition analysed using 16S rRNA gene sequencing. We observed a consistently high alpha diversity and relative abundance of bacteria normally found in soil and vegetation. We also found that inactivation of BDB by autoclaving effectively inactivates human and murine bacteria, viruses and parasites. Finally, we demonstrate that experimental mice prone to develop IMIDs (non-obese diabetic, NOD, mouse model) can be exposed to BDB without causing adverse effects on animal health and welfare. Our study provides insights into a potentially safe, sustainable, and cost-effective approach for simulating exposure to natural microbiota, which could have substantial impacts on health and socio-economic factors.
Keywords: biodiversity hypothesis; environmental microbiota; microbial exposure; natural material; microbial diversity; soil